A∞ and AN formulations of the linear transport equation in heterogeneous media. (January 2016) - Coppa, G.
Highlights: A new formulation of the A ∞ method for heterogeneous media is proposed. The kernel of transport equation is approximated as a sum of pure exponential terms. The transport problem is reduced to coupled equations for homogeneous media. Four approximations are proposed and the relative equations are presented in detail. Abstract: The aim of the paper is to provide a contribution for the extension to heterogeneous media of the A ∞ and A N formulations for the linear transport equation. A new approach is proposed, in which the exponential of the optical length is decomposed in a sum of pure exponential terms, as in a homogeneous medium; in this way, a set of coupled diffusion-like equations is obtained. Different approximations are presented and their validity is discussed.